MENTAL HEALTH DISORDERS AFFECTING ATHLETES AFTER CAREER TERMINATION: INTERVENTIONS SUPPORTING PSYCHOLOGICAL ADAPTATION — A SYSTEMATIC REVIEW - Kwiecien, Julia; Stołtny, Julia; Mida, Magdalena; Maruszak, Anna; Michalik, Magdalena; Majda, Urszula; Lisik, Magdalena; Goryczka, Justyna; Kimla, Witold; Hajok, Natalia (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Loss of athletic identity — following retirement, athletes often lose the central element that previously defined their lives. This loss may lead to an identity crisis and significant emotional difficulties. Numerous studies indicate that former athletes are at an increased risk of developing depression, anxiety, and substance use disorders, particularly during the initial years after the end of their athletic careers. Objective: The aim of this paper is to conduct a literature review on mental health disorders observed in athletes following retirement from professional sport, and to evaluate the effectiveness of various psychological, social, and medical interventions that support adaptation to post-athletic life. Materials and methods: The study is based on a variety of analyses from 2007 to 2026 that were found using PubMed and Google Scholar. Results: Research findings indicate that former athletes constitute a high-risk group for mood disorders and adjustment difficulties. Effective interventions include psychological support programs, psychoeducational interventions, development of non-sport-related skills, and social and vocational support. Conclusion: Psychological support during the transition period following athletic retirement should be systemic and long-term. Integrating psychological interventions with career development programs can significantly enhance the well-being of former athletes.